2021
DOI: 10.1186/s13014-021-01808-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hypofractionation and standard fractionation for post-prostatectomy salvage radiotherapy in patients with persistent PSA: single institution experience

Abstract: Background Hypofractionated post-prostatectomy radiotherapy is emerging practice, however with no randomized evidence so far to support it’s use. Additionally, patients with persistent PSA after prostatectomy may have aggressive disease and respond less well on standard salvage treatment. Herein we report outcomes for conventionally fractionated (CFR) and hypofractionated radiotherapy (HFR) in patients with persistent postprostatectomy PSA who received salvage radiotherapy to prostate bed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…As previously discussed, the use of higher dose per fraction has been also proposed for RMS as a consequence of the low a/b ratio (2.8 Gy) shown for this cancer type (79). However, the use of HFRT for the treatment of RMS did not lead to any improvement in efficacy (58-70), as already described for other cancer types (80)(81)(82)(83)(84). Despite being a milestone in the multimodal treatment of pediatric RMS, RT is still significantly associated with local failure in most cases of tumor relapse, and the RMS response to radiation appears to go far beyond the simple dose problem.…”
Section: The Radiobiology Of Rms: the Linear Quadratic Model And The ...mentioning
confidence: 86%
“…As previously discussed, the use of higher dose per fraction has been also proposed for RMS as a consequence of the low a/b ratio (2.8 Gy) shown for this cancer type (79). However, the use of HFRT for the treatment of RMS did not lead to any improvement in efficacy (58-70), as already described for other cancer types (80)(81)(82)(83)(84). Despite being a milestone in the multimodal treatment of pediatric RMS, RT is still significantly associated with local failure in most cases of tumor relapse, and the RMS response to radiation appears to go far beyond the simple dose problem.…”
Section: The Radiobiology Of Rms: the Linear Quadratic Model And The ...mentioning
confidence: 86%
“…From the view of the salvage radiation aspect, Murgic et al. [ 56 ] further explored that for those patients with persistent postoperative PSA, a standard fractionation RT regimen was associated with higher biochemical control compared to a commonly used hypofractionated regimen, which may be due to the higher biological dose. Additionally, they also found that the first post-prostatectomy PSA level, rather than the pre-RT PSA level, is an important prognostic factor for the success of SRT.…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of a normofractionated regimen (66 Gy in 33 fractions) over a hypofractionated scheme (52.5 Gy in 20 fractions) in the biochemical control of disease is reported by Murgic et al [44] According to the Authors the superiority of the normofractionated regimen is the result of the lower biological dose of the hypofractionated schedule compared to the normofractionated. Other major limitations reported by the Authors are the baseline imbalance in ADT use, ADT duration, and ISUP grade group distribution between the two radiotherapy cohorts.…”
Section: In a Study Of Moderate Hypofractionation With 3d-conformal R...mentioning
confidence: 96%